2016
DOI: 10.1007/s00439-016-1722-2
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in CIT, encoding citron rho-interacting serine/threonine kinase, cause severe primary microcephaly in humans

Abstract: Primary microcephaly is a clinical phenotype in which the head circumference is significantly reduced at birth due to abnormal brain development, primarily at the cortical level. Despite the marked genetic heterogeneity, most primary microcephaly-linked genes converge on mitosis regulation. Two consanguineous families segregating the phenotype of severe primary microcephaly, spasticity and failure to thrive had overlapping autozygomes in which exome sequencing identified homozygous splicing variants in CIT tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…Indeed, four recent studies have reported that mutations in CIT are responsible for some cases of primary microcephaly in humans (Basit et al, 2016;Harding et al, 2016;Li et al, 2016;Shaheen et al, 2016), thereby, further supporting this hypothesis and, for the first time, linking CIT-K to human disease. In both rodents and humans, the defects in CNS development were associated with failure of cytokinesis and severe apoptosis.…”
Section: Cit-k and Diseasementioning
confidence: 63%
See 4 more Smart Citations
“…Indeed, four recent studies have reported that mutations in CIT are responsible for some cases of primary microcephaly in humans (Basit et al, 2016;Harding et al, 2016;Li et al, 2016;Shaheen et al, 2016), thereby, further supporting this hypothesis and, for the first time, linking CIT-K to human disease. In both rodents and humans, the defects in CNS development were associated with failure of cytokinesis and severe apoptosis.…”
Section: Cit-k and Diseasementioning
confidence: 63%
“…Second, it will be important to establish tools, such as small-molecule inhibitors and analogue-sensitive mutants, to address the role of its kinase activity in vivo. Third, we do not know why CIT-K is necessary in every tissue in fly (D'Avino et al, 2004;Naim et al, 2004;Shandala et al, 2004), whereas it appears to be more important for the normal development and function of the CNS in mammals (Basit et al, 2016;Di Cunto et al, 2000Harding et al, 2016;Li et al, 2016;Shaheen et al, 2016), despite the fact that its depletion causes cytokinesis failure in different types of human cultured cell ( . This discrepancy between in vivo an ex vivo model systems might simply reflect a difference in the requirement of CIT-K and midbody formation in cultured cells versus whole tissues.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 98%
See 3 more Smart Citations